BarrettNET—a prospective registry for risk estimation of patients with Barrett's esophagus to progress to adenocarcinoma. Issue 8 (24th April 2019) - Wiethaler, Maria; Slotta-Huspenina, Julia; Brandtner, Anna; Horstmann, Julia; Wein, Frederik; Baumeister, Theresa; Radani, Nikole; Gerland, Sophie; Anand, Akanksha; Lange, Sebastian; Schmidt, Melissa; Janssen, Klaus-Peter; et al.
SUMMARY: Risk stratification in patients with Barrett's esophagus (BE) to prevent the development of esophageal adenocarcinoma (EAC) is an unsolved task. The incidence of EAC and BE is increasing and patients are still at unknown risk. BarrettNET is an ongoing multicenter prospective cohort study initiated to identify and validate molecular and clinical biomarkers that allow a more personalized surveillance strategy for patients with BE. For BarrettNET participants are recruited in 20 study centers throughout Germany, to be followed for progression to dysplasia (low-grade dysplasia or high-grade dysplasia) or EAC for >10 years. The study instruments comprise self-administered epidemiological information (containing data on demographics, lifestyle factors, and health), as well as biological specimens, i.e., blood-based samples, esophageal tissue biopsies, and feces and saliva samples. In follow-up visits according to the individual surveillance plan of the participants, sample collection is repeated. The standardized collection and processing of the specimen guarantee the highest sample quality. Via a mobile accessible database, the documentation of inclusion, epidemiological data, and pathological disease status are recorded subsequently. Currently the BarrettNET registry includes 560 participants (23.1% women and 76.9% men, aged 22–92 years) with a median follow-up of 951 days. Both the design and the size of BarrettNET offer the advantage of answering research questions regarding potential causes of disease progression from BE to EAC. Here all the integrated methods and materials of BarrettNET are presented and reviewed to introduce this valuable German registry.